Perbandingan Penggunaan Model Pembelajaran Creative Problem Solving dan Problem Based Learning Terhadap Hasil Belajar Peserta Didik Pada Materi Bioteknologi Kelas Ix di Smpn 01 Tarowang Kabupaten Jeneponto (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the learning outcomes of students taught using the Creative Problem Solving (CPS) learning model, the learning outcomes of students taught using the Problem Based Learning (PBL) learning model, and a comparison of the learning outcomes between the two models. This study used a quasi-experimental method with a Non-Equivalent Control Group Design. The research subjects consisted of two experimental classes, namely experimental class 1 which used the CPS model and experimental class 2 which used the PBL model. The results showed that the average learning outcome score of students in experimental class 1 was 84.7, while in experimental class 2 it was 81. The t-test produced a significance value of 0.001 < 0.05, which means that there was a significant difference in learning outcomes between students taught using the CPS and PBL learning models. Thus, it can be concluded that the CPS model provides higher learning outcomes than the PBL model.